Toxicological Effects of Mycotoxins on Target Cells - Juan-García, Ana (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Mycotoxins are a Public Health concern that in last year have reached the top 10 food and product hazard categories in the Rapid Alert System for Food and Feed (RASFF), with almost six hundred notifications. The toxicological effects of mycotoxins are evaluated through the extrapolation of results from in vivo and in vitro assays. Studies of mycotoxins' effects at the cellular level precede those in organs and systems. All these studies are key steps for risk assessment and following legislation for mycotoxins. This Special Issue of Toxins comprises 10 original contributions and two reviews. The Issue reports new findings regarding toxic mechanisms, the use of innovative techniques to study the potential toxicity of mycotoxins not only individually but in combination, reflecting a real scenario according to current studies of mycotoxins.